Neuronal regulation of innate lymphoid cells. (February 2019) - Klose, Christoph SN; Artis, David
Abstract : The cardinal signs of inflammation suggest a close connection between the nervous system and the immune system. However, the cellular and molecular basis of these interactions remains incompletely defined. Recent research has demonstrated that tissue-resident innate lymphoid cells (ILCs) obtain neuronal signals, particularly at mucosal barriers, where ILCs regulate tissue homeostasis. New developments in our understanding of neuronal regulation of ILCs provide insight into how immune responses in tissues are precisely targeted, spatially regulated, and how ILCs sense environmental changes and disturbance of tissue homeostasis. Therefore, neuronal regulation of immune responses is emerging as an important signaling hub for the maintenance of tissue integrity.